2018
DOI: 10.1038/s41467-018-03420-8
|View full text |Cite
|
Sign up to set email alerts
|

Cascading lake drainage on the Greenland Ice Sheet triggered by tensile shock and fracture

Abstract: Supraglacial lakes on the Greenland Ice Sheet are expanding inland, but the impact on ice flow is equivocal because interior surface conditions may preclude the transfer of surface water to the bed. Here we use a well-constrained 3D model to demonstrate that supraglacial lakes in Greenland drain when tensile-stress perturbations propagate fractures in areas where fractures are normally absent or closed. These melt-induced perturbations escalate when lakes as far as 80 km apart form expansive networks and drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 59 publications
4
94
2
Order By: Relevance
“…The longitudinal coupling effect observed here may be part of a catchment‐wide phenomenon that is governed by melt‐induced perturbations from surface water forming and reaching the bed, which propagate upglacier through the course of the summer melt season. A detailed numerical analysis of the longitudinal coupling effect by Christoffersen et al () supports the vertical thickening observed throughout the ice column starting in July at S30. Here widespread melt occurring at the surface lubricates the bed at S30, encouraging faster velocities, while ice flow at lower elevations becomes markedly slower in response to the formation of an efficient basal drainage system from large, continued meltwater influx into the subglacial environment.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The longitudinal coupling effect observed here may be part of a catchment‐wide phenomenon that is governed by melt‐induced perturbations from surface water forming and reaching the bed, which propagate upglacier through the course of the summer melt season. A detailed numerical analysis of the longitudinal coupling effect by Christoffersen et al () supports the vertical thickening observed throughout the ice column starting in July at S30. Here widespread melt occurring at the surface lubricates the bed at S30, encouraging faster velocities, while ice flow at lower elevations becomes markedly slower in response to the formation of an efficient basal drainage system from large, continued meltwater influx into the subglacial environment.…”
Section: Discussionmentioning
confidence: 65%
“…The lower degree of viscosity attributed to Wisconsin ice facilitates enhanced deformation, in contrast to the Holocene ice residing above this layer. The latter, being more viscous and cold, may thus act as a stiff beam, which accommodates the far‐field transfer of stresses via longitudinal coupling (Christoffersen et al, ). The latter plays a crucial role in the force balance of the ice sheet in summer but may also be important in winter and spring, when a significant increase in the water pressure inside small basal cavities reduces the basal traction, resulting in faster glacier motion.…”
Section: Discussionmentioning
confidence: 99%
“…High discharge into moulins from supraglacial streams (Smith et al, ) are particularly important in the LG catchment at lower elevations (Clason et al, ). Above 1,000 m, supraglacial lake drainage events become increasingly important (Clason et al, ), and Q rates can change rapidly when supraglacial lakes drain from the ablation zone during the outburst period (i.e., outburst events) (Bartholomew et al, ; Christoffersen et al, ). These drainage events are characterized by rapid changes in SPM concentrations and SpC (Bartholomew et al, ), as stored waters at the bed are evacuated by incoming supraglacial water (Hatton et al, ), and thus may coincide with compositional changes in DOM in subglacial outflow.…”
Section: Discussionmentioning
confidence: 99%
“…• High-elevation firn-aquifer water drainage drives evolution of the subglacial hydrologic system >30 km inland, potentially affecting outlet glacier speed • Persistent input of water from firn aquifers can maintain subglacial channels outside the melt season and across years • The timing and duration of firn-aquifer water delivery to the bed is an important but underconstrained variable in ice sheet hydrology Firn aquifers currently occupy areas low in the accumulation zone around much of the Greenland Ice Sheet (Miège et al, 2016), with inland expansion anticipated in future warm climates . If new surface-to-bed connections are made at inland locations, the subsequent evolution of the subglacial hydrologic system may alter ice dynamics (e.g., Bartholomew et al, 2011b;Christoffersen et al, 2018;Clason et al, 2015;Doyle et al, 2014;Poinar et al, 2015). Here, we implement a modeling study whereby a series of idealized scenarios drain surface water to the bed at low-elevation locations and at higher elevations through the downstream end of a firn aquifer.…”
Section: 1029/2019gl082786mentioning
confidence: 99%